How badly do we need theory Z? - D'Andrade, Kendall (Journal of business ethics, 1986)
In Theory Z-style management everybody participates in corporate decision making. This more open process should give us fewer Pintos, Love Canals, and massive international payoffs as executives are forced to expose their reasoning to the moral sensibilities of the whole corporation. So far everything looks good. But we are a long way from showing that only corporations so managed can be fully moral. Yet Dwiggins seems to believe this, putting his faith in the basic goodness of the many while virtually dismissing the managers as mere technicians. This is too slick; even if it describes our average corporation today, there are plenty of less radical changes which can also produce the desired moral corporation. Good leadership which acts on their commitment to improve the company is surely one historically respectable alternative; cynicism about the present crop of leaders should not distract us from investigating this route. Finally, I wonder if Dwiggins can consistently urge us to embrace a full-scale Theory Z organizational structure, given his position on the place of ethics and profitability.